Differences in Experiences With the Development of Mixed-Use Projects From 2004 and 2017 - Metzinger, Jamie (Frontiers in Built Environment, 2021)
Mixed-use developments, having three or more uses within one development, have several benefits for communities, however due to the complexity of these developments, several challenges arise in the planning and development phases. The main challenges are local regulations, neighborhood opposition, financing, and insufficient market interest. A 2004 survey of these challenges was repeated in 2017 and the differences between the two are compared in this paper. Significant differences were found in the frequencies of the challenges, mainly that the frequency proportion has dropped in 2017. However, local regulations remained the most significant challenge encountered. The decrease in frequencies is conceivably a sign that regulators, financers, and members of the community are becoming more familiar with mixed-use developments.